Diabetes Food Plan - Waisundara, Viduranga (IntechOpen, 2018)
Diabetes is a global pandemic where many remedies have been recommended as means of combating the prevalence of this disease. However, dietary control appears to be more effective than others. This book focuses on interventions concerning glycemic control, the oxidative stress-based occurrence of the disease and its prevention, as well as novel remedies. While many books have been published recently on this aspect, the book aims to serve as an update to the scientific community, as well as to those who have been adversely affected by the disease. There are many unexplored territories when it comes to diabetes, and it is hoped that this publication will open up new avenues of successfully curbing its occurrence.